2018
DOI: 10.1111/petr.13299
|View full text |Cite
|
Sign up to set email alerts
|

When does vesicoureteral reflux in pediatric kidney transplant patients need treatment?

Abstract: Purpose The treatment of VUR in children with UTI has changed significantly, due to studies showing that antibiotic prophylaxis does not decrease renal scarring. As children with kidney transplants are at higher risk for UTI, we investigated if select patients with renal transplant VUR could be managed without surgery. Materials and Methods A total of 18 patients with VUR into their renal grafts were identified, and 319 patients underwent transplantation from 2006 to 2016. The cause for the detection of the VU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 35 publications
0
19
1
Order By: Relevance
“…In addition to results in "uncomplicated" VUR, numerous studies have provided evidence that endoscopic injection is also effective in specific patient populations that may be deemed more difficult to treat (historically not considered for endoscopic therapy). These include high-grade VUR, duplicated systems, adult women and kidney transplant patients (85,86,(89)(90)(91)(92)(93)(94)(95)(96)(97)(98)(99)(100)(101)(102)(103)(104). Resolution rates may be reduced in these groups of patients: for example, Läckgren et al reported a positive response rate of 63% in patients with duplicated ureters, compared with 68% in the broader population of VUR patients (104,105).…”
Section: Endoscopic Injectionmentioning
confidence: 99%
“…In addition to results in "uncomplicated" VUR, numerous studies have provided evidence that endoscopic injection is also effective in specific patient populations that may be deemed more difficult to treat (historically not considered for endoscopic therapy). These include high-grade VUR, duplicated systems, adult women and kidney transplant patients (85,86,(89)(90)(91)(92)(93)(94)(95)(96)(97)(98)(99)(100)(101)(102)(103)(104). Resolution rates may be reduced in these groups of patients: for example, Läckgren et al reported a positive response rate of 63% in patients with duplicated ureters, compared with 68% in the broader population of VUR patients (104,105).…”
Section: Endoscopic Injectionmentioning
confidence: 99%
“…While endoscopic subureteric injections of dextranomer/hyaluronic acid may be considered, success rates in correcting post-Tx VUR have been low, and their use has been associated with many complications. 71,73 POSTTRANSPLANT OUTCOMES When comparing outcomes in children with and without urologic causes of ESRD, most studies have shown comparable graft or patient survival in children with CA-KUT, 74 in spite of higher risk of post-Tx UTIs, even in the presence of severe bladder dysfunction. 75,76 Therefore, for pediatric patients with advanced CKD and ESRD due to CAKUT, Tx is the goal for renal replacement therapy because of the better long-term survival, growth and development, and quality of life after Tx than remaining on maintenance dialysis.…”
Section: Managing Bladder Dysfunctionmentioning
confidence: 99%
“…Hydroureteronephrosis (HUN) of renal transplant (RT) can occur secondary to ureteral obstruction or vesicoureteral reflux (VUR) [1,2]. However, secondary megaureter of various etiologies, neurogenic bladder, loss of ureteral tonicity following denervation, and polyuric states can also present with non-obstructive non-refluxing transplant HUN [3].…”
Section: Introductionmentioning
confidence: 99%